Wobble Board and Theraband Exercise for Dynamic Stabilization in Chronic Ankle Instability - Meiza Anniza; Mutiarahmi; Arfian Hamzah; Nafi’ah; Enny Fauziah (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
Dynamic stabilization disorders frequently occur among athletes as a consequence of Chronic Ankle Instability (CAI), which arises from recurrent ankle sprains resulting in ligament damage and diminished ankle function. Effective management is therefore required to enhance proprioception through wobble board exercise and to improve muscular strength through theraband exercise, thereby increasing overall ankle stabilization. This case study investigated the physiotherapy management of dynamic stabilization disorders attributable to CAI using combined wobble board exercise and theraband exercise interventions conducted at Monsphysio Handil Bakti Clinic. Dynamic stabilization was measured using the Y Balance Test over a four-week treatment period. The results demonstrated a progressive improvement in dynamic stabilization, with the Y Balance Test composite score increasing from 86.7% at baseline (Week I) to 93.7% after four weeks of intervention (Week IV), representing an absolute improvement of 7.0 percentage points. These findings suggest that the combined intervention of wobble board exercise and theraband exercise yields weekly improvements in dynamic stabilization among patients with CAI. Future researchers are recommended to conduct studies with longer treatment durations and to control for patient activity levels, which may influence treatment outcomes.